APPLICATION OF THE LAW ON CORRUPTION CRIMINAL ACTS IN HANDLING BANKING CRIMES AT PT BRI (PERSERO) TBK UNIT GEMOLONG 1 SRAGEN IN THE FRAMEWORK OF SAVED STATE FINANCES - Suwardi, Didi; Bowo Suharto, Rakhmat (Jurnal Hukum Khaira Ummah, 2023)
The study is a critical study of the implementation of the Corruption Act in order to save the state finances (Case Study Against Corruption at PT BRI (Persero) Tbk Gemolong Unit 1 Sragen). The results of the study found that 1) The occurrence of irregularities in the granting of People's Business Loans at PT BRI (Persero) Tbk Gemolong I Sragen Unit that is the target of large credit distribution, frequency many, simple conditions and field officers are limited without balanced the system of adequate control. In addition, the existence of moral elements hazzard, namely the occurrence of collusion. 2) The application of the Corruption Crime Act in the handling of Banking Crime in the Court of Corruption, namely Defendant CHOYUM MUFIDAH, SE Binti SULAIMAN has been proven legally and convincingly guilty of committing a crime as violated Article 3 Paragraph (1) jo. Article 18 Paragraph (1) Sub-Paragraph a and b of Law of the Republic of Indonesia Number 31 Year 1999 concerning the Eradication of Corruption which has been amended by Law of the Republic of Indonesia Number 20 Year 2001 regarding Amendment to Law of the Republic of Indonesia Number 31 Year 1999 regarding Eradication of Corruption jo. Article 55 Paragraph (1) to-1 of the Criminal Code jo article 64 paragraph (1) of the Criminal Code in Subsidair indictment. 3) Obstacles in the application of the Corruption Act in the handling of Banking Crime at PT BRI (Persero) Tbk Gemolong Unit 1 Sragen in order to save the State Finance that the Public Prosecutor can not prove primary claims.Keywords: Corruption,Â  Banking Crime